1978
DOI: 10.1007/bf00278728
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of two French Guiana Amerindian populations

Abstract: Phenotypes and gene frequencies are presented for 20 serum and erythrocyte proteins in two Amerindian populations of inner French Guiana. No genetic variability was detected in 12 of these systems. Heterozygosity was calculated for the others and the reasons for its variation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The variability observed in the third component of complement was unex pected, since in four other tribes (Cuiva, Emerillon, Oiampi and Shuara) only C3S has been found [Goeddeet al, 1977;Tchen et al, 1978Tchen et al, , 1979. Since all of them live in northern South America (Ecuador, Vene zuela and French Guiana), this finding may reflect heterogeneity between nor thern and southern Indian populations.…”
Section: Resultsmentioning
confidence: 89%
“…The variability observed in the third component of complement was unex pected, since in four other tribes (Cuiva, Emerillon, Oiampi and Shuara) only C3S has been found [Goeddeet al, 1977;Tchen et al, 1978Tchen et al, , 1979. Since all of them live in northern South America (Ecuador, Vene zuela and French Guiana), this finding may reflect heterogeneity between nor thern and southern Indian populations.…”
Section: Resultsmentioning
confidence: 89%
“…The Gm and Km allotypes were determined by the classical hemagglutination inhibition method, with human antisera (Field and Dugoujon, 1989). The transferrin, Rhesus ''d,'' PGM2, and G2M*23 markers were excluded from the statistical analysis due to their monomorphism in South American Indians (Tchen et al, 1978a(Tchen et al, ,b, 1981Salzano et al, 1988). The ABO and Kell systems, which are also monomorphic in South American Indians, were included to evaluate admixture.…”
Section: Methodsmentioning
confidence: 99%
“…Primary data concerning the French Guiana Indians have been collected as early as the 1960s (Larrouy et al, 1964a,b;Bois and Feingold, 1972;Daveau et al, 1975;Tchen et al, 1978aTchen et al, ,b, 1981Dugoujon et al, 1994aDugoujon et al, ,b, 1995; nevertheless, they have been unequally examined as compared with other South American Indian populations. Indeed, no relevant DNA studies are available for these populations.…”
mentioning
confidence: 99%
“…The number of non-Indian subjects tested in South America (23,839) is about 40% higher than the total number of Indians (Table 2). There are now 13 variants that (1994); Krahó, 193, Neel (1978); Macushi, 694, Neel et al (1977), Salzano et al (1984); Mundurucu, 361, Salzano et al (1991), Santos et al (1998); Noanama, 155, Kirk et al (1974); Pacaá s Novos, 222, Salzano et al (1985b); Palikour, 115, Santos et al (1998); Parakanã , 252, Black et al (1980Black et al ( , 1988; Quechua, 39, Modiano et al (1972); Sateré-Mawé, 170, Salzano et al (1985a);Surui, 198, Callegari-Jacques et al (1994), Salzano et al (1998); Tenharim, 20, Santos et al (1998);Ticuna, 761, Neel et al (1980); Urubu-Kaapor, 205, Black et al (1988); Waiã pi, 361, Tchen et al (1978), Black et al (1983); Wai Wai, 166, Callegari-Jacques et al (1996); Zoró, 76, Salzano et al (1998 Tables 1 and 2 is more meaningful when considered in the context of the information provided in Tables 3 and 4. The provisional assignment of Belém 2 to albumin México by direct electrophoretic comparisons in four buffer systems is rendered plausible by previous studies in which the structural studies confirmed the electrophoretic findings (see Arai et al, 1989), as well as by the present results concerning albumin Fortaleza.…”
Section: Resultsmentioning
confidence: 99%